Forests influence yeast populations vectored by insects into vineyards - Valentini, Beatrice; Barbero, Francesca; Casacci, Luca Pietro; Luganini, Anna; Stefanini, Irene (Frontiers in Microbiology, 2022)
In the vineyard, yeast communities impact the ripening and fermentation of grapes and are influenced by geographical location, climate, and soil characteristics. Despite the great advancement in our knowledge of the vineyard mycobiota, a key step of the process leading to the definition of the vineyard yeast community is still poorly understood: if geography, climate, and soil influence the mycobiota, potentially through selection, where do the yeast originate from, and how can they reach the vineyard? In this perspective, it is currently acknowledged that forests host several yeast species and that insects, particularly social wasps, can vector and maintain the yeasts known to populate the vineyard. Alas, the conveyance, fostered by insects, of yeasts from the forest to the vineyard has not been proven yet. In this study, we aimed to assess the existence of links between a potential natural source of yeasts (woods), the vectors (social wasps), and the composition of the vineyard mycobiota. For this purpose, the mycobiota of wasps caught in six Italian vineyards were analyzed over two years through culturomics approaches. The results clearly indicate that the presence of wooded areas close to vineyards is associated with particular features of the mycobiota vectored by social wasps. Wasps caught in vineyards near wooded areas bear a higher number of yeast cells and higher biodiversity than insects caught in vineyards far from woods. Furthermore, insects caught in vineyards close to woods bear distinctive yeast populations, encompassing species such as Saccharomyces cerevisiae. Overall, our work provides fundamental insights into the ecology of the vineyard mycobiota and highlights the need to maintain a vineyard-woodland mosaic landscape, thus preserving the suitable habitat for yeast species relevant to wine-making.